The effect of qualitative exercises in developing motor compatibility and learning the skill of volleyball jump set - Shaalan, Riyadh A.; Aboode , Muthana A.; Radhi, Mahmoud Nasser (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
This study aims to prepare and identify the effect of qualitative exercises in order to develop motor compatibility and learning the skill of jump set in volleyball. The present study had an experimental design. Specialized School in Al-Qadisiyah Governorate was identified as the research community for the current study. A total of 28 players were recruited as the participants for the present study. Participants were allocated into two groups, i.e. experimental group and the control group, by simple random allocation method (raffle). Based on the findings of the study, it was concluded that the qualitative exercises helped the players in developing motor compatibility, i.e. the motor coordination of the legs and arms of the experimental group, and also that the qualitative exercises helped in learning the technical performance of the jump set skill in volleyball for the experimental group. The researchers recommend to use qualitative exercises according to the level of learners in learning the jump set skill in volleyball.